Antibacterial Screening of Lippia origanoides Essential Oil on Gram-negative Bacteria - de Andrade, Rodrigo Marcelino Zacarias; Santos, Bernardina de Paixão; Silva, Roberson Matteus Fernandes; Silva, Mateus Gonçalves; Oliveira, Igor de Sousa; Ferreira, Sávio Benvindo; Lira, Rafaelle Cavalcante (Archives of Pharmacy and Pharmaceutical Sciences, 2024)
Essential oils (EO) are extracted from different plant species and can be present in different plant organs. Rosemary-pepper EO is composed of around 50% to 70% thymol, a phenolic compound proven to be active against fungi and bacteria. The active components present in these compounds can affect the vital functionality of bacterial cells, leading to protein denaturation and cell lysis. Therefore, the present study aims to evaluate in vitro the antibacterial potential of Lippia origanoides EO against gram-negative bacteria. This is an exploratory study, with a technical-experimental procedure, with a quantitative approach, carried out at the Federal University of Campina Grande. The strains used were Pseudomonas aeruginosa ATCC 27853, <Proteus mirabilis ATCC 25933, and Escherichia coli ATCC 25922, using concentrations of 1024, 512, 256, and 128 μg/ml using the disc diffusion method in triplicate. After the incubation period, the formation of halos of bacterial growth inhibition was not observed. There are possible causes for the lack of antibacterial activity of the EO concerning the strains of gram-negative bacteria used in the study, including the possibility of not containing components with antibacterial properties in concentrations sufficient for the expected activity at the concentrations tested. Based on the results obtained, the Rosemary-Pepper EO (Lippia organoids) did not demonstrate antimicrobial activity against the gram-negative bacteria used in the study. Therefore, the development of new research with Lippia origanoides essential oil with gram-positive bacteria is suggested.